Answer:
b. 6.65%
Step-by-step explanation:
Note: The organized question is attached below
Yield of maturity = [(1+forward rate of years 1) * (1+forward rate of years 2) * (1+forward rate of years 3) * (1+forward rate of years 4)]^(1/4) - 1
Yield of maturity = [(1+5.8%) * (1+6.4%) * (1+7.1%) * (1+7.3%)]^(1/4) - 1
Yield of maturity = (1.058 * 1.064 * 1.071 * 1.0730)^(1/4) - 1
Yield of maturity = 1.293649093296^(1/4) - 1
Yield of maturity = 1.06648345438 - 1
Yield of maturity = 0.06648345438
Yield of maturity = 6.6483%
Yield of maturity = 6.65%